Membangun Keunggulan Kompetitif dengan Sistem Informasi Manajemen yang Efektif - Indah Nirwana Sari; Rayyan Firdaus (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
In this digital era, business competition is increasingly fierce and complex. A company's ability to adapt and innovate is key to achieving competitive advantage. An effective Management Information System (MIS) plays an important role in supporting business processes and strategic decision-making. This research aims to analyze how SIM can help companies build competitive advantage through literature study and qualitative analysis. The results of this study show that SIM can help companies build competitive advantage in various ways. By utilizing SIM effectively, companies can improve efficiency, increase productivity, improve the quality of decision-making, and support innovation. This can ultimately help companies achieve success in this competitive digital era.